Ethical Judgment Manajer Terhadap Praktik Earnings Management - Mahfud Sholihin; Ainun Na’im (The Indonesian Journal of Accounting Research, 2013)
Earnings management is an important, but controversial, issue in the business. While the majority of previous studies on the topic view from economic perspective, this current study investigates from ethical perspective. Specifically, this current study examines the ethical judgment of managers on various dimensions of earnings management practices.This study hypothesizes that difference types, materiality, periods of effect, consistency with generally accepted accounting principles, directions, and objectives of earnings management does not have effects on managers ethical judgment. The results, based on responses from managers studying at Master of Management Program, Gadjah Mada University, show that the types,materiality, and period of effect of earnings management have effects on the ethical judgment of the managers on the practice. On the other hand,a consistency with generally accepted accounting principles, directions, and objective of earnings management does not have effect on the judgment.